Physical workload and accelerated occurrence of lumbar spine diseases: risk and rate advancement periods in a German multicenter case-control study - Andreas Seidler; Ulrike Euler; Ulrich Bolm-Audorff; Rolf Ellegast; Joachim Grifka; Johannes Haerting; Matthias Jäger; Martina Michaelis; Oliver Kuss (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVE: In a German multicenter case-control study of lumbar disc diseases, we calculated risk and rate advancement periods (RAP) for physical workload. METHODS: Patients aged 25-70 years with clinically and radiologically verified lumbar disc herniation (286 males, 278 females) or symptomatic lumbar disc narrowing (145 males, 206 females) were compared with population control subjects (453 males and 448 females). For this analysis, all manual handling of objects of about ≥5 kg and postures with trunk inclination of ≥20 °, as assessed by technical experts, were included in the calculation of cumulative lumbar load, determined by biomechanical model calculations. Logistic regression analysis was applied to calculate RAP, adjusted for region. RESULTS: We found a steep positive dose-response relationship between age and lumbar disc narrowing among men as well as women; however, we did not find a monotonic increase in lumbar disc herniation risk with age. As a monotonic increase in disease risk with age constitutes a fundamental assumption underlying the RAP concept, we restricted our RAP analysis to cases with symptomatic lumbar disc narrowing. Among men, there was a positive dose-response relationship between the cumulative lumbar load and the acceleration of lumbar disc narrowing. In the highest exposure category, a RAP of 28.0 years [95% confidence interval (95% CI) 9.7-46.3 years] was found. Among women, the RAP was 8.8 years (95% CI 2.4-15.2 years) in the highest exposure category. CONCLUSION: This study emphasizes the conceptual importance of risk acceleration - causation not only comprises the occurrence of a disease (that without a specific exposure would not have occurred at all) but also the accelerated occurrence of a disease (that without exposure would have occurred later in life).